Impact of GDP and RES Share on CO2 Emissions, Energy Efficiency and Economic Growth in European Union Member States - Szczubełek, Grzegorz; Rzeczkowski, Daniel (Olsztyn Economic Journal, 2024)
Economic growth and CO2 emissions are closely linked to energy consumption. Energy transition towards renewable energy sources (RES) and improving energy efficiency are crucial to combating global warming. EU member states are striving to reduce CO2 emissions while supporting economic growth. However, it is necessary to develop an understanding of how both gross domestic product (GDP) level and RES share affect energy efficiency and CO2 emissions. The purpose of this paper is to analyse the impact of the GDP level and the renewable energy sources (RES) share on CO2 emissions, energy efficiency, and economic growth in European Union states. The study employs structural equation modelling (SEM) using the partial least squares (PLS) method. The analysis is based on data collected from Eurostat, the OECD and other sources covering the period 2004-2023. The paper constitutes a substantial contribution to the body of literature by providing a comprehensive analysis of the impact of GDP level and the share of renewable energy sources (RES) on CO2 emissions, taking into account energy efficiency and urbanisation as key factors. The study revealed that a high level of GDP combined with a high share of RES in the energy mix is conducive to a more effective reduction of CO2 emissions. Furthermore, urbanisation has a varying impact on economic growth depending on the level of GDP and the share of RES. This points to the need to take the state’s specifics into account when developing energy policies. The findings may provide policymakers with some guidelines when shaping energy and environmental strategies in EU states.